UTILISING THE PROFESSIONAL POTENTIAL OF THE ELDERLY IN THE PROCESS OF CONSTRUCTION OF SILVER ECONOMY IN POLAND - Niewiadomska, Anna; Sobolewska-Poniedziałek, Ewa (Acta Scientiarum Polonorum. Oeconomia, 2015)
The issue of professional activity of the elderly is currently the subject of intense debate. The projected decline in the population of young people makes it necessary to raise the level of professional involvement of the more mature part of the labour force. The increase in the economic activity of people aged 50+ is seen as an opportunity to preserve the continuity of economic growth. This paper explores the issue of the possibility of utilizing the professional potential of elderly people in the context of the construction of silver economy, paying attention to the possible benefits stemming from the implementation of its principles.